RBPs: an RNA editor’s choice - Fierro-Monti, Ivo (Frontiers in Molecular Biosciences, 2024)
RNA-binding proteins (RBPs) play a key role in gene expression and post-transcriptional RNA regulation. As integral components of ribonucleoprotein complexes, RBPs are susceptible to genomic and RNA Editing derived amino acid substitutions, impacting functional interactions. This article explores the prevalent RNA Editing of RBPs, unravelling the complex interplay between RBPs and RNA Editing events. Emphasis is placed on their influence on single amino acid variants (SAAVs) and implications for disease development. The role of Proteogenomics in identifying SAAVs is briefly discussed, offering insights into the RBP landscape. RNA Editing within RBPs emerges as a promising target for precision medicine, reshaping our understanding of genetic and epigenetic variations in health and disease. Main 1. The Ubiquitous Role of RBPs in Gene Expression Regulation. RNA-binding proteins (RBPs) are integral to gene expression regulation. Defined by their ability to bind RNA, many of them through modular RNA-binding domains (RBDs), they also contain conserved structural motifs enhancing RNA specificity and functional versatility. About 14 to 32% of human protein-coding genes encode RBPs [1][2][3][4][5][6]. RBPs can be classified based on four interaction categories: RNA motif-dependent, RNA structure-dependent, RNA modificationdependent, and RNA guide-based interactions [7]. These interactions form ribonucleoprotein (RNP) complexes, modulated by RNA through riboregulation, where RNA controls protein function by direct, specific binding. Dysregulated RBPs are linked to diseases such as cardiovascular and peripheral vascular diseases, diabetes, cancer, neurodegenerative diseases, and autoimmune disorders [8][9][10][11][12][13]. RBPs recognise and interact with numerous transcripts via RBDs, forming regulatory networks